Towards quasi isotropic laminates with engineered fracture behaviour for industrial applications. (8th September 2018) - Bullegas, Gianmaria; Benoliel, Jacob; Fenelli, Pier Luigi; Pinho, Silvestre T.; Pimenta, Soraia
Abstract: Carefully placed patterns of micro-cuts have been inserted in the microstructure of Cross-Ply (CP) and Quasi-Isotropic (QI) thin-ply CFRP laminates to engineer their translaminar fracture behaviour with the purpose of increasing their damage resistance under different loading conditions. A novel Finite Fracture Mechanics model has been developed to predict the translaminar crack propagation behaviour and to guide the microstructure design. This technique led to a 68% increase in the laminate notched strength, and a 460% increase in the laminate translaminar work of fracture during Compact Tension tests for CP laminates. It also allowed to achieve a 27% increase in the laminate notched strength, and a 189% increase in the translaminar work of fracture during Compact Tension tests for QI laminates. Furthermore, an increase of 43% in the total energy dissipated, and of 40% in maximum deflection at complete failure was achieved during quasi-static indentation tests on QI laminates. Given the significant improvements in the mechanical performance under different loading conditions, and the industrial relevance of QI laminates and the increasing industrial interest in thin-ply laminates, these results demonstrate that microstructure design can be used effectively to improve the damage tolerance of CFRP structures in industrially-relevant applications.